2018
DOI: 10.29252/jafm.11.03.27945
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Boltzmann Numerical Investigation of Inner Cylindrical Pin-fins Configuration on Nanofluid Natural Convective Heat Transfer in Porous Enclosure

Abstract: Concerning the geometrical effect of inner cylindrical hot pins, the natural convective heat transfer of nanofluid in a homogenous porous medium in a squared enclosure is numerically studied, using lattice Boltzmann method (LBM). In order to investigate the arrangement of inner cylinders for better heat transfer performance, five different configurations (including one, three, and four pins) were compared, while the total heat transfer area of inner pins were held fixed. Squared cavity walls and inner cylinder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Recently, a considerable literature has grown up around the theme of nanofluid heat transfer enhancement (Ganvir et al, 2017;Jafari et al, 2018;Ma et al, 2018;Ma et al, 2020;Sepehrnia et al, 2021;Wang et al, 2020). Qi et al (2017) Izadi et al (2018) to increase the energy transference performance in a square chamber.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a considerable literature has grown up around the theme of nanofluid heat transfer enhancement (Ganvir et al, 2017;Jafari et al, 2018;Ma et al, 2018;Ma et al, 2020;Sepehrnia et al, 2021;Wang et al, 2020). Qi et al (2017) Izadi et al (2018) to increase the energy transference performance in a square chamber.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a considerable literature has grown up around the theme of nanofluid heat transfer enhancement (Ganvir et al , 2017; Jafari et al , 2018; Ma et al , 2018; Ma et al , 2020; Sepehrnia et al , 2021; Wang et al , 2020). Qi et al (2017) analyzed the energy transport characteristics of CPU under an influence of Al 2 O 3 /H 2 O and TiO 2 /H 2 O nanoliquids.…”
Section: Introductionmentioning
confidence: 99%
“…At first, LBM lattice algorithm was mainly used to simulate isothermal flow. With the continuous development, various models suitable for heat transfer problems have been developed, which are mainly divided into multi velocity model, double distribution function model and mixed model [9]. Moreover, these models are widely used in different engineering thermophysical research problems, including natural convection simulation, mixed convection simulation, micro channel flow and heat transfer simulation, multi-component multiphase flow and heat transfer simulation, etc [10].…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that instability threshold is delayed with the increment in fin density. Jafari et al (2018) has presented the numerical study on flow and heat transfer of a Nano fluid between a cold square enclosure and warm inner cylindrical pin-fins system filled with homogenous porous media using Lattice Boltzmann method and found increment in Rayleigh number and volume fraction of nanoparticles and further recommended it for heating the cold square enclosure. With an aim to enhance the heat transfer rate from a plate to fluid (air), a staggered arrangement of semi-circular pin fins are considered.…”
Section: Introductionmentioning
confidence: 99%